Inequality and Poverty across Generations in the European Union - Chen, Tingyun (Staff Discussion Notes; Staff Discussion Notes ;, 2018)
This SDN studies the evolution of inequality across age groups leading up to and since the global financial crisis, as well as implications for fiscal and labor policies. Europe's population is aging, child and youth poverty are rising, and income support systems are often better equipped to address old-age poverty than the challenges faced by poor children and/or unemployed youth today.